Analysis of assembly defects in the cam curved groove mechanism. Issue 1 (28th December 2020) - Lan, Weibin; Fan, Shouwen; Fan, Shuai
Abstract : Purpose: This paper aims to propose an elementary approach toward the identification of assembly defects of a cam curved groove mechanism. Design/methodology/approach: A numerical analysis method for identifying the assembly defects of the cam curved groove mechanism is proposed by resorting to Hertz contact theory. A general mathematical model is established to analyze the kinematic and dynamic characteristics with an interference fit between the main roller and cam curved groove, including the contact points of the external and internal ring. Findings: The analysis method of the contact point characteristics of the cam curved groove mechanism is given in this paper, and the kinematic and dynamic characteristics of the main roller can be analyzed. The numerical examples presented in this paper are implemented in MATLAB, feasibility and validity of the above algorithm are verified by the finite element method. Originality/value: Regarding the defects of the interference fit, the findings of this paper can serve as a reference for researchers in reducing the defects in the design process of the cam mechanism.